12 x^-2 y^4 /{ -3 x (y^-7) } ??
is
-4 x^-3 y^11
= -4 y^11/x^3
Simplify. Do not use negative exponents in the answer.
12x-2y4
-3xy-7
There should be a line between like a fraction but it did not copy or paste.
This is the answer I got
12 x^-2 y^4 = 12y^4/x^2
-3xy^-7 = -3x/y^7
it was wrong.
12x^-2y^4 / -3xy^-7
= 12/-3 * x^-2 / x * y^4/y^-7
If you have a base with negative exponent, you move to the other side of the fraction bar to make it positive.
= -4 1/x^2 x * y^4 y^7/1
When you multiply exponents with bases, you add the exponents. Now you similfy it to get the final answer.
Please help. This is my last class to graduate and I have been trying to figure it out for two days. Thanks
2 answers
HEY, you were almost there!
-4 1/x^2 x * y^4 y^7/1
-4 *1/(x^2*x) * y^(4+7)
= -4 y^11/x^3
-4 1/x^2 x * y^4 y^7/1
-4 *1/(x^2*x) * y^(4+7)
= -4 y^11/x^3